2018
DOI: 10.18805/lr-3939
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo evaluation of different fungicides, plant extracts, bio-control agents and organics amendments for management of dry root rot of chickpea caused by Macrophomina phaseolina

Abstract: The present study was planned to evaluate the efficacy of various fungicides, plant extracts, biocontrol agents and oil cakes against Macrophomina phaseolina causing dry root rot of chickpea. Among the tested biocontrol agents against Macrophomina phaseolina, T. viride was found the most effective against the fungus followed by T. harzianum, Bacillus subtalis and P. fluorescens was the least effective in reducing root rot incidence. Among the fungicides carbendazim was found most effective and recorded minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Also results reported by Kaurav et al, (2019) showed that neem inhibited the growth of Rhizoctonia bataticola. Results were also in agreement with findings of Lakhran et al, (2020), Brahmbhatt and Aravind (2018) who showed that T. viride was found the most effective against the fungus and neem was most effective in reducing the root rot. Manjunatha et al, (2013) reported that seed treatment using T. viride can be used under field conditions to control dry root rot of chickpea.…”
Section: Resultssupporting
confidence: 91%
“…Also results reported by Kaurav et al, (2019) showed that neem inhibited the growth of Rhizoctonia bataticola. Results were also in agreement with findings of Lakhran et al, (2020), Brahmbhatt and Aravind (2018) who showed that T. viride was found the most effective against the fungus and neem was most effective in reducing the root rot. Manjunatha et al, (2013) reported that seed treatment using T. viride can be used under field conditions to control dry root rot of chickpea.…”
Section: Resultssupporting
confidence: 91%
“…It was closely followed by tebuconazole 50%+ trifloxystrobin 25% WG as seed treatment with soil application of P. fluorescens @ 10kg/ha. Similar results were obtained by Meena et al (2018), Veena and Reddy (2016) and Lakhran and Ahir (2020).…”
Section: Management Of Dry Root Rot Of Chickpea By Bioagents and Fung...supporting
confidence: 89%
“…Parthenium leaf extract, at a dosage of 15%, was found to exhibit 75.2% inhibition. Similarly, garlic extract, showed predominant in reducing the occurrence of root rot caused by M. phaseolina, followed by neem leaf extract (Lakhran et al 2020).…”
Section: Discussionmentioning
confidence: 97%